Sterile Endophthalmitis after Intravitreal Injections - Joaquín Marticorena; Vito Romano; Francisco Gómez-Ulla (Hindawi Limited, 2012)
Sterile endophthalmitis appears as an infrequent complication of intravitreal injections and seems to develop mainly in the context of the off-label use of drugs that have not been conceived for intravitreous administration. The aetiology of sterile endophthalmitis, independently of the administered drug, remains uncertain and a multifactorial origin cannot be discarded. Sterile inflammation secondary both to intravitreal triamcinolone acetonide and to intravitreal bevacizumab share many characteristics such as the acute and painless vision loss present in the big majority of the cases. Dense vitreous opacity is a common factor, while anterior segment inflammation appears to be mild to moderate. In eyes with sterile endophthalmitis, visual acuity improves progressively as the intraocular inflammation reduces without any specific treatment. If by any chance the ophthalmologist is not convinced by the sterile origin of the inflammation, this complication must be treated as an acute endophthalmitis because of the devastating visual prognosis of this intraocular infection in the absence of therapy.